The USA Methodology to Use Smart Force in the War on Syria (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The complex nature of the security threats faced by the international environment forced the American administration to develop reconciliation strategies that integrate several methods (traditional and modern) into one proposal، enabling it to implement its goals، especially in the region. This was demonstrated in the smart power strategy for optimal use of available tools، where American foreign policy is based on interests and strengthening the global position in a way that achieves leadership in world leadership. American strategic thought sees that the world is looking for a political leader، and that the United States of America is the leader، given that it possesses the elements of smart power. The United States has decided to link its security to the security of the Middle East region، given the region’s unique location and strategic depth that is important to it. The use of smart force by the United States of America towards Syria falls within the framework of achieving a number of goals، such as working to undermine the capabilities and capabilities of Syria and its allies، and to dismantle Syria and its ability to threaten the security and safety of its strategic ally (the Zionist entity). All of this reflects the extent of the success of the United States of America in controlling the international system، controlling changes، and its central role in international crises in the foreseeable future.